2017
DOI: 10.4103/ijpc.ijpc_53_17
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual needs and quality of life of patients with cancer

Abstract: Background and Aim:Information about spiritual needs and quality of life (QoL) is limited in Iranian cancer patients. This study was conducted to determine the relationship between spiritual needs and QoL among cancer patients in Iran.Methods:This correlational study included a convenience sample of 150 eligible cancer patients who were hospitalized in the oncology wards and outpatient clinics. Using two questionnaires; the spiritual needs survey and the European Organization for Research and Treatment of Canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Recently, an Indonesian study with 308 breast cancer inpatients found that spirituality was positively related with emotional well-being and affected physical discomfort by mediating their emotional condition (Nuraini et al, 2018). Other studies also pointed out that the unmet spiritual needs of cancer patients affect their health care decision making, decrease life quality, and make them dissatisfied with care (Astrow et al, 2018;Balboni & Balboni, 2019;Forouzi et al, 2017).…”
Section: Spiritual Needsmentioning
confidence: 99%
“…Recently, an Indonesian study with 308 breast cancer inpatients found that spirituality was positively related with emotional well-being and affected physical discomfort by mediating their emotional condition (Nuraini et al, 2018). Other studies also pointed out that the unmet spiritual needs of cancer patients affect their health care decision making, decrease life quality, and make them dissatisfied with care (Astrow et al, 2018;Balboni & Balboni, 2019;Forouzi et al, 2017).…”
Section: Spiritual Needsmentioning
confidence: 99%
“…However, the spiritual needs of patients with cancer are high, as reported by Forouzi et al . [14] Despite the fact that nurses are familiar with the importance of providing spiritual care, they are not able to comprehensively meet the spiritual needs of patients;[15] similarly, 96% of physicians believe in the important impact of spirituality on health, but these needs are not met[16] due to specific barriers, including nurse and physician perspectives and beliefs and values regarding spiritual care. Determining health-care providers’ perspectives on spiritual care is the first step to facilitating the provision of such care.…”
Section: Introductionmentioning
confidence: 99%
“…Each clinician is responsible for approaching the patient as a whole person and to provide relational, dignity-based, compassionate care [3]. Holistic care requires that spiritual needs of patients would be addressed and satisfied by healthcare professionals [17] in collaboration with social care and clergy staff and patient relatives.…”
Section: Discussionmentioning
confidence: 99%
“…For patients and caregivers, it is sometimes difficult to define what spiritual needs and what spiritual care does mean for them. Spiritual needs of cancer patients may have a wide spectrum of queries starting with religious rituals and talks with faith community members, followed by the relationship with family members and friends; gratitude, hope, and forgiveness; loving others; particular connection with nature in a religious or nonreligious way; or deep self-assessment and piece with oneself [13,14,15,16,17,18]. Assessment of the spiritual needs of patients is complicated because of the ambiguity and complexity of the concept of spirituality and difficulties in differentiating between the concepts of religion and spirituality, especially when assessing spirituality in patients who are not religious.…”
Section: Introductionmentioning
confidence: 99%